1996
DOI: 10.1097/00004728-199601000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Breast Microcalcifications: Evaluation by Dynamic Contrast-Enhanced Subtraction MRI

Abstract: Poor specificity limits the diagnostic accuracy of dynamic contrast-enhanced subtraction MRI in distinguishing benign from malignant microcalcifications on mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 7 publications
0
40
0
2
Order By: Relevance
“…Because DCIS is the earliest stage of breast cancer and has the best prognosis, it is likely that further improvements in the detection of breast cancers at a preinvasive stage may improve patient outcomes. Some reports have shown decreased diagnostic accuracy of DCE MR imaging for DCIS (2,3), while others have shown comparable or even higher performance compared with that of x-ray mammography (4,5). The sensitivity of DCE MR imaging for detection of DCIS may be compromised if the lesion does not exhibit sufficient gadolinium uptake or if it is obscured by strongly enhancing parenchyma (6,7).…”
Section: C3mentioning
confidence: 99%
“…Because DCIS is the earliest stage of breast cancer and has the best prognosis, it is likely that further improvements in the detection of breast cancers at a preinvasive stage may improve patient outcomes. Some reports have shown decreased diagnostic accuracy of DCE MR imaging for DCIS (2,3), while others have shown comparable or even higher performance compared with that of x-ray mammography (4,5). The sensitivity of DCE MR imaging for detection of DCIS may be compromised if the lesion does not exhibit sufficient gadolinium uptake or if it is obscured by strongly enhancing parenchyma (6,7).…”
Section: C3mentioning
confidence: 99%
“…Dynamic enhancement rates of DCIS are extremely variable [16], but morphological criteria such as segmental or linear enhancement have been reported to be the imaging hallmarks of DCIS on breast MRI [15,[17][18][19][20][21][22][23]. However, the positive predictive value of this enhancement pattern is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Westerhof et al (1998), investigating mammographically suspicious microcalcifications, reported a sensitivity of 45%, specificity of 72%, positive predictive value of 71%, negative predictive value 46% and an accuracy of 56%, and in a further study, Gilles et al observed a sensitivity of 95% and a specificity of 51%. Their specificity was impaired because the presence or absence of contrast uptake in the breast was the only parameter used to decide if the area of microcalcification was associated with malignancy or not (Gilles et al, 1996).…”
Section: Dcismentioning
confidence: 99%